PENGUJIAN PENGENDALIAN INTERNAL TERHADAP PERSEDIAAN BARANG DAGANG - wibowo, heri; Yonita, Ariska (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2024)
The Tunjung Baru Building Store is a private company engaged in the field of trading companies selling building raw materials. This building shop relies on a lot of inventory in its sales cycle, which is one of the important assets for the company. The role of internal control over inventory in a building store is very important to improve inventory safety. The data analysis technique uses audit techniques for merchandise inventory, namely checking the internal control of merchandise inventory using Internal Control Questionnaires, drawing conclusions, examining purchase and sale transactions, and checking inventory physical counts (stock taking). The sample in this study was 131 transactions, consisting of 40 types of goods in merchandise purchase transactions and 91 types of goods in merchandise inventory sales transactions. Calculation of the level of effectiveness using the slovin formula. The results of the compliance test on the level of effectiveness of merchandise inventory at the Tunjung Baru Building Store in the February 2023 period were 59%, which means that internal control is running quite effectively. Management of merchandise inventory carried out by employees is also in accordance with applicable procedures. The results of the substantive test are in accordance with the physical records in the warehouse and accounting records related to the purchase and sale of merchandise. The calculation has been carried out mathematically and has been affixed with a paid off stamp and the signature of the relevant party and authorization has been carried out from the store management.